Improved Resistance to Controlled Deterioration in Transgenic Seeds - Prieto-Dapena, Pilar (American Society of Plant Biologists, 2006)
We show that seed-specific overexpression of the sunflower (Helianthus annuus) HaHSFA9 heat stress transcription factor (HSF) in tobacco (Nicotiana tabacum) enhances the accumulation of heat shock proteins (HSPs). Among these proteins were HSP101 and a subset of the small HSPs, including proteins that accumulate only during embryogenesis in the absence of thermal stress. Levels of late embryogenesis abundant proteins or seed oligosaccharides, however, were not affected. In the transgenic seeds, a high basal thermotolerance persisted during the early hours of imbibition. Transgenic seeds also showed significantly improved resistance to controlled deterioration in a stable and transgene-dependent manner. Furthermore, overexpression of HaHSFA9 did not have detrimental effects on plant growth or development, including seed morphology and total seed yield. Our results agree with previous work tentatively associating HSP gene expression with phenotypes important for seed longevity. These findings might have implications for improving seed longevity in economically important crops.